A brave heart [videorecording (DVD)] : the Lizzie Velasquez story - Velasquez, Lizzie (Women Rising Corporation, 2015)
"A documentary following the life of Lizzie Velasquez, her triumphant journey to the other side of bullying, and her mission to inspire and empower a more positive online environment."--IMDb